Contextualizing Cost System Design: A Literature Review - Shahinaz M. Ibrahim; Ibrahim M. El Sibai; Bassant Badr El Din (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - What are the measures or proxies used to evaluate Cost System Design (CSD) performance in the literature? What are the contextual factors studied in relation to CSD in the literature? Motivation - Evaluating the effectiveness of a cost system design should be linked to how the cost information produced would impact managerial decision making in an organization. Unfortunately there are no common measures or proxies for evaluating CSD functionality across different studies and contexts. This calls for further research for defining evaluative criteria suitable for various cost systems in addition to exploring the varying impact of different contextual factors on CSD. Idea - This paper reviews how CSD functionality measurement have changed over time reflecting different relationships with various contextual factors through analysing and synthesising extant cost accounting literature Data - Review of relevant papers reporting empirical results (quantitative and qualitative) published in various accounting journals during the periods of 1987 to 2020. Tools - Qualitative review of relevant papers Findings - The review revealed that majority of the studies are contingency based, CSD sophistication measurement evolved from distinct choices of cost systems to more structural characteristics and critical attributes of system characteristics. The paper points out to the need for more comprehensive conclusive framework for evaluating CSD performance assessing the impact of different contextual factors on cost system functionality and firm performance. Contribution - This review contributes to existing cost accounting literature by reviewing and analysing different measures of CSD functionality in general without stressing a particular cost system.
Keywords: M41; 650; cost system design; cost system sophistication; contextual factors; contingency theory; literature review